Respuesta :
Answer:
Step-by-step explanation:
−5(2)(−4)=2(x−8)
Simplify both sides of the equation.
−5(2)(−4)=2(x−8)
−5(2)(−4)=(2)(x)+(2)(−8)(Distribute)
40=2x+−16
40=2x−16
Step 2: Flip the equation.
2x−16=40
Step 3: Add 16 to both sides.
2x−16+16=40+16
2x=56
Step 4: Divide both sides by 2.
2x/2 = 56/2
x=28
Distribute the -5 to 2x and -4 which would be: -10x+20=2(x-8)
Then distribute the 2 to x and -8 which would be: -10x+20=2x-16
Subtract 20 from both sides:-10x+20=2x-16
-20. -20
10x= 2x-36
Subtract 2x from both sides: -10x=2x-36
-2x. -2x
-12x=-36
Divide -12 from both sides: -12x=-36
-12/-12= -36/-12
So in the end x=3
Then distribute the 2 to x and -8 which would be: -10x+20=2x-16
Subtract 20 from both sides:-10x+20=2x-16
-20. -20
10x= 2x-36
Subtract 2x from both sides: -10x=2x-36
-2x. -2x
-12x=-36
Divide -12 from both sides: -12x=-36
-12/-12= -36/-12
So in the end x=3